Vaccination programs and infectious disease burden among military personnel: a systematic review with pathogen-specific quantitative synthesis - Muhammad Sobri Maulana; Dwitia Pratiwi; Arditya Prayogi (Perkumpulan Kedokteran Militer, 2026)
Introduction: Military personnel are highly exposed to vaccine-preventable infections because of close living conditions, rapid mobilization, deployment to endemic areas, and intense training schedules. This systematic review and meta-analysis evaluated whether vaccination programs reduce infectious disease burden among military personnel. Methods: PubMed/MEDLINE, Embase, Cochrane Library, ProQuest, and Scopus were searched from database inception to 16 May 2026 for comparative studies of vaccination programs in military populations. Eligible outcomes were laboratory-confirmed infection, clinical disease, acute respiratory illness, meningococcal disease, or program-defined infectious disease burden. Random-effects meta-analysis was performed using log risk ratios. Results: Sixteen studies were included in the qualitative synthesis and 13 contributed quantitative data. Across adenovirus, meningococcal, influenza, and COVID-19 vaccination programs, the pooled risk ratio was 0.19 (95% confidence interval 0.11-0.32), corresponding to an approximate 81% reduction in infectious disease burden. Subgroup effects were strongest for adenovirus and meningococcal vaccination programs and more moderate for influenza vaccination. Discussion: The findings support vaccination as a high-impact readiness intervention in military settings, especially for pathogens amplified by recruit training environments. Certainty was limited by heterogeneity, pre-post designs, historical evidence, and inconsistent reporting of denominators. Conclusion: Vaccination programs substantially reduce infectious disease burden among military personnel. Future research should use prospective surveillance, standardized case definitions, pathogen-specific laboratory confirmation, and transparent reporting of denominators and person-time.